Tinjauan Hukum Tindak Pidana Penadahan oleh Karyawan PT Prima Jaya (Putusan No.2811/2016) - Nasution, Nanda Syahra; Hasibuan, A Lawali; Munthe, Riswan (Universitas Medan Area, 2024)
This study aims to analyze the factors that cause the crime of speedometer theft by employees of PT. Prima Jaya Perkasa based on Decision No. 2811/Pid.B/2016/PN. MDN. In addition, this study also aims to evaluate the imposition of criminal sanctions against the perpetrators of these criminal acts, as stated in the relevant court decisions, focusing on the aspect of conformity between the sanctions given and the provisions of the applicable criminal law. This study analyzes the crime of arrest based on Article 480 of the Criminal Code with a normative-empirical juridical approach. The data were analyzed qualitatively to evaluate the relationship between legal norms and judicial practice. The goal is to recommend improvements in criminal law enforcement. The results of the study show that the crime of stealing a speedometer by an employee of PT. Prima Jaya Perkasa is triggered by internal factors, such as economic pressure and low education, as well as external factors, such as a poor social environment and technological advancements. The imposition of a sentence of 1 year and 6 months based on Article 480 paragraph (1) of the Criminal Code reflects efforts to uphold justice and provide a deterrent effect. Prevention through legal education, economic strengthening, and internal supervision is needed to minimize similar cases in the future.